T-lex2: genotyping, frequency estimation and re-annotation of transposable elements using single or pooled next-generation sequencing data - Fiston-Lavier, Anna-Sophie (Nucleic Acids Res, 2015)
Transposable elements (TEs) constitute the most active, diverse and ancient component in a broad range of genomes. Complete understanding of genome function and evolution cannot be achieved without a thorough understanding of TE impact and biology. However, in-depth analysis of TEs still represents a challenge due to the repetitive nature of these genomic entities. In this work, we present a broadly applicable and flexible tool: T-lex2. T-lex2 is the only available software that allows routine, automatic and accurate genotyping of individual TE insertions and estimation of their population frequencies both using individual strain and pooled next-generation sequencing data. Furthermore, T-lex2 also assesses the quality of the calls allowing the identification of miss-annotated TEs and providing the necessary information to re-annotate them. The flexible and customizable design of T-lex2 allows running it in any genome and for any type of TE insertion. Here, we tested the fidelity of T-lex2 using the fly and human genomes. Overall, T-lex2 represents a significant improvement in our ability to analyze the contribution of TEs to genome function and evolution as well as learning about the biology of TEs. T-lex2 is freely available online at http://sourceforge.net/projects/tlex.